Generalized Life-Time Model for Cold Extrusion Tools - Cser, L; Geiger, Manfred (CIRP Annals - Manufacturing Technology, 1991)
It is very difficult to predict the expected life time at cold extrusion because of die complexity of interchanges among the different kinds of failures and failure mechanisms. To the prediction of the most probably life time for a class of cold forming tools an expert system bas been developed which takes into account the geometrical, mechanical and inbological boundary conditions and utilizes factory data and experience. In order to be able to handle the different mechanisms of failure it was necessary to work out a generalized life-time model of cold forming dies. The governing idea is similar on the state-space method used in the qualitative reasoning. All the damage mechanisms are active at the same time, but the life-time is determined by the dominant mechanism leading fastest to the total fall out of the die. The role of the dominant mechanism can be taken over by other mechanisms during the exploitation of the die, depending on the changes in the state variables. The expert system is based on the feature processing. The tool is divided into the elements carrying not only geometric information, but information about the loads and the possible failure also. The elements of the same tool part are connected with each other by different types of contact and neighbours between the elements of different tool parts. © 1991 CIRP.
LFT Import::2019-07-15 (231)
Keywords: EXPERT SYSTEM; EXTRUSION; FORMING; TOOL-LIFE